Pool boiling heat transfer of ferrofluids on structured hydrophilic and hydrophobic surfaces: The effect of magnetic field - ÖZDEMİR, MEHMED RAFET (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2020)
The combined effect of external magnetic field and surface modification on boiling heat transfer of ferrofluids was investigated in this study. Experiments were performed on suspensions of Fe3O4 nanoparticles (volume fraction of 0.025% vf%) with and without presence of magnetic field on structured (surfaces with artificial cavities) hydrophilic and hydrophobic surfaces. Surface related effects such as the hole diameter, pitch size and surface wettability on boiling heat transfer were revealed using the high speed camera system. According to the obtained results, application of magnetic field enhanced boiling heat transfer. The effect of magnetic field was more pronounced on surfaces with larger pitch sizes. Magnetic field promoted bubble nucleation on the superheated surfaces by generating an additional force via Fe3O4 nanoparticles, resulting in enhanced bubblebubble interactions and coalescence. Furthermore, the surfaces with the larger cavity diameter performed better in terms of heat transfer. Scanning Electron Microscopy (SEM) images showed that as the cavity diameter decreased, deposited nanoparticles tended to completely fill the cavities on hydrophilic surfaces and thus deteriorate boiling heat transfer. On hydrophobic surfaces, deposition of nanoparticles led to a biphilic surface, thereby enhancing boiling heat transfer. As the cavity size increased, smaller portion of the cavities was filled with nanoparticles, and nucleation could still occur from the nucleation sites.
Keywords: Artificial cavity; Magnetic field; Ferrofluid; Boiling heat transfer; Bubble dynamics; Surface wettability; CELL TRACKING VELOCIMETRY; CHF ENHANCEMENT; NANOFLUID; FLUX; PERFORMANCE; MICRO